2019
DOI: 10.1186/s12889-019-7106-5
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Coverage among Children with and without Intellectual Disabilities in the UK: Cross Sectional Study

Abstract: Background Universal childhood vaccination programmes form a core component of child health policies in most countries, including the UK. Achieving high coverage rates of vaccines is critical for establishing ‘herd immunity’ and preventing disease outbreaks. Evidence from the UK has identified several groups of children who are at risk of not being fully immunised. Our aim was to determine whether children with intellectual disabilities constitute one such group. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Vaccination rates among people with intellectual disability have been little investigated. A recent study found that vaccination coverage among UK children with intellectual disability were lower than among other children, 26 and vaccination coverage for hepatitis B and influenza among children and adolescents with intellectual disability in Taiwan was also lower than for those without intellectual disability 27,28 . A recent review that more broadly examined vaccination status in people with disability found that knowledge in this area was inadequate 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination rates among people with intellectual disability have been little investigated. A recent study found that vaccination coverage among UK children with intellectual disability were lower than among other children, 26 and vaccination coverage for hepatitis B and influenza among children and adolescents with intellectual disability in Taiwan was also lower than for those without intellectual disability 27,28 . A recent review that more broadly examined vaccination status in people with disability found that knowledge in this area was inadequate 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The first category consisted of largely quantitative studies: nine surveys or analyses focusing only on uptake of the MMR vaccine, and potential inequalities or predictive demographic factors therein. Some of the studies used private longitudinal health data such as the Millennium Cohort Study of ~19,000 children born in 2000–1 [ 31 , 32 ] or the Secure Anonymised Information Linkage (SAIL) databank of 800,000 children living in Wales [ 33 ]. Others used public National Health Service (NHS) health data through the Child Health Information Systems [ 34 , 35 , 36 ], the Scottish Immunisation and Recall System (SIRS) [ 37 ], primary care data of the Clinical Practice Research Datalink (CPRD) [ 38 ] or the Cover of Vaccination Evaluated Rapidly (COVER) dataset produced by Public Health England (PHE) [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Perry et al [ 36 ] found that children of asylum seekers in Wales had lower rates of uptake compared to the general population, albeit with some variation between different areas of Wales due to limitations in the outreach resources of each local health authority. Emerson et al [ 31 ] focused on children with intellectual disabilities and found that they were at increased risk for low uptake, although this may be partially explained by the inverse association between intellectual disabilities and family socioeconomic position. Osam et al [ 38 ] used primary care data from 400,000 mother–baby pairs and found that maternal mental illness, even when adjusting for deprivation factors, had a significant negative effect on routine MMR vaccine uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Perry et al [34] found that children of asylum seekers in Wales had lower rates of uptake compared to the general population, albeit with some variation between different areas of Wales due to limitations in the outreach resources of each local health authority. Emerson et al [29] focused on children with intellectual disabilities and found that they were at increased risk for low uptake, although this may be partially explained by the positive association between intellectual disabilities and lower family socioeconomic position. Osam et al [36] used primary care data from 400,000 motherbaby pairs and found that maternal mental illness, even when adjusting for deprivation factors, had a significant negative effect on routine MMR vaccine uptake.…”
Section: Uptake and Demographics -9 Studiesmentioning
confidence: 99%